2019
DOI: 10.1136/neurintsurg-2019-014890
|View full text |Cite
|
Sign up to set email alerts
|

An interdisciplinary approach to inhospital stroke improves stroke detection and treatment time

Abstract: BackgroundInhospital stroke (IHS) is associated with high morbidity and mortality, likely related to multiple factors, including delayed time to recognition, associated comorbidities, and initial care from non-stroke trained providers. We hypothesized that guided revision of a formalized ‘stroke code’ system can improve diagnosis and time to thrombolysis and thrombectomy.MethodsIHS activations occurring at a comprehensive stroke center between 2013 and 2016 were retrospectively analyzed to guide revisions of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…All the articles were case-control observational studies with a IIIb level of evidence. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 Critical appraisal classified all the included studies as “good” quality ( Supplemental Table 3 , available online at http://www.mcpiqojournal.org ). The interobserver agreement for selecting the relevant studies to be included was excellent ( k =0.78).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the articles were case-control observational studies with a IIIb level of evidence. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 Critical appraisal classified all the included studies as “good” quality ( Supplemental Table 3 , available online at http://www.mcpiqojournal.org ). The interobserver agreement for selecting the relevant studies to be included was excellent ( k =0.78).…”
Section: Resultsmentioning
confidence: 99%
“…In this group, the most common changes implemented were EMS before notification (n=3), a rapid triage protocol and stroke team notification (n=3), modified CT flow (n=3), and a team-based approach (n=3). Manners et al 29 appeared to select the most effective combination of strategies (SMD=1.41), which included the implementation of a stroke severity scale, direct communication between the rapid response and neurology teams, and the neurology team meeting the patient directly in the radiology department. 29 The remaining multiple-strategy studies had a similar level of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Additional challenges include less stroke education for key multidisciplinary teams and lack of multidisciplinary assessment and workflow after a stroke alert, in-hospital stroke kits for rapid intravenous thrombolysis, and standardized computerized physician order entry sets. 10,21,30,52 Studies consistently demonstrate that community hospitals have less consistent adherence to treatment guidelines. 2,3 Telemedicine may be beneficial in bridging the gap when medical expertise is needed, and models to enhance coverage should be explored.…”
Section: Challenges Limitations and Stroke Systems Of Carementioning
confidence: 99%
“…An interdisciplinary team that follows appropriate specialized protocol for patients with IHIS, including a special contact window for emergent liaison, rapid transportation of patients for cranial imaging study, and a clear pathway for medicine delivery to the bed side, has been reported to effectively shorten the intrahospital delay. 16,34 Furthermore, widespread educational programs for all hospital staff to more effectively recognize stroke symptoms, rapidly convey the bedside information from caregivers to physicians in charge, and understand the concept of therapeutic time windows, are vital for increasing the reperfusion rate for eligible patients. Stroke incidence is lower in the ward than in the ED.…”
Section: Dovepressmentioning
confidence: 99%